Is informality a good measure of job quality? Evidence from job satisfaction data - Carmen Pagés; Lucía Madrigal (Inter-American Development Bank, Research Department, 2008)
The formality status of a job is the most widely used indicator of job quality in developing countries. However, a number of studies argue that, at least for some workers, the informality status may be driven by choice rather than exclusion. This paper uses job satisfaction data from three low-income countries (Honduras, Guatemala and El Salvador) to assess whether informal jobs are less valued than formal jobs. The paper finds substantial differences in job satisfaction within different types of informal jobs. More importantly, the results suggest that across different definitions, informality does not yield the same ranking of job quality as self-reported measures of job satisfaction. This correspondence varies across countries, and it seems to be lower for less-skilled workers.
Keywords: J21; J28; O17; 330; Job Satisfaction; Informality; Quality of Employment; Honduras; El Salvador; Guatemala